Simulation of Direct Digital Synthesizer with LabView - Elan Djaelani Suardja (IPTEK Journal of Proceedings Series, 2014)
Direct Digital Synthesizer (DDS) is a frequency synthesizer to generate an arbitrary waveform. It is widely used for telecommunication applications such as RADAR and JAMMER. Nowadays, DDS is preferred than its traditional counterpart, the phase-locked loop (PLL). However, the price of DDS is still relatively expensive. For this reason, it is important to develop a simulation for DDS as a cheaper alternative to learn about DDS, especially for students. National Instrument (NI) has developed a simulation for DDS. However, this simulation may not accessible for student either. In this research, a simulation for Direct Digital Synthesizer (DDS) is developed. The DDS simulation developed by the National Instrument is improved by adding new features. The added features are the storage system, an integrated DAC and the use of 20 bit data for lookup.